Fluorescent properties of DNA base analogue tC upon incorporation into DNA--negligible influence of neighbouring bases on fluorescence quantum yield. - Sandin, P; Wilhelmsson, L; Lincoln, P; Powers, V; Brown, T; Albinsson, B (2005)
The quantum yield of the fluorescent tricyclic cytosine analogue, 1,3-diaza-2-oxophenothiazine, tC, is high and virtually unaffected by incorporation into both single- and double-stranded DNA irrespective of neighbouring bases (0.17-0.24 and 0.16-0.21, respectively) and the corresponding fluorescence decay curves are all mono-exponential, properties that are unmatched by any base analogue so far. The fluorescence lifetimes increase when going from tC free in solution (3.2 ns) to single- and double-stranded DNA (on average 5.7 and 6.3 ns, respectively). The mono-exponential decays further support previous NMR results where it was found that tC has a well-defined position and geometry within the DNA helix. Furthermore, we find that the oxidation potential of tC is 0.4 V lower than for deoxyguanosine, the natural base with the lowest oxidation potential. This suggests that tC may be of interest in charge transfer studies in DNA as an electron hole acceptor. We also present a novel synthetic route to the phosphoramidite form of tC. The results presented here together with previous work show that tC is a very good C-analogue that induces minimal perturbation to the native structure of DNA. This makes tC unique as a fluorescent base analogue and is thus highly interesting in a range of applications for studying e.g. structure, dynamics and kinetics in nucleic acid systems.